Pneumonia Karena Migrasi Larva Toxocara sp.dan Ancylostoma sp. pada Kucing Domestik - Br Sitepu, Dinda Meilinda; Putriningsih, Putu Ayu Sisyawati; Widyastuti, Sri Kayati (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2025)
A 2-year-old domestic cat named Simba presented with respiratory symptoms, including coughing and nasal discharge containing serous exudate. Additionally, the cat exhibited abdominal enlargement. During the physical examination, palpation of the trachea triggered a coughing reflex, and the cat appeared to be attempting to expel something from its throat. Fecal examination revealed the presence of Toxocara sp. and Ancylostoma sp. eggs. A routine hematology test showed leukocytosis, lymphocytosis, monocytosis, granulocytopenia. The cat was diagnosed with pneumonia caused by the migration of Toxocara sp. and Ancylostoma sp. larvae.Treatment was given with Pyrantel pamoate (Combantrin®) 125 mg/tab with a dose of 40 mg (1/3 tab) orally once a week for two weeks, repeating depending on the severity, Amoxyclav antibiotic 625 mg/tab with a dose of 64 mg (1/10) orally twice a day for 7 days, and fish oil (Tung-hai Fish Liver Oil®) orally one soft gel per day for 7 days. An evaluation on the seventh day showed that the cat’s condition had improved.